PERANCANGAN SISTEM IoT PADA SMART DOOR LOCK MENGGUNAKAN APLIKASI BLYNK - Kaleb Yefune Sun; Yonky Pernando; M. Ibnu Safari (JUTSI: Jurnal Teknologi dan Sistem Informasi, 2021)
Abstract: This review portrays the plan of IoT on Keen entryway locks are keys that can be utilized to make a commonsense and productive security framework in homes and different structures. The update highlight is added with Remote. Remote is an electromagnetic telecom network that utilizations waves rather than links. The motivation behind this Keen Entryway Lock is to expand proficiency and diminish manual opening from within, however if you open the entryway from an external perspective, it is sufficient to utilize a cell phone. in the investigation, when a guest came, the guest saw a sensor warning before the entryway and afterward moved toward the notice sensor that had been planned with the past blynk application, the blynk application sent a notice through a cell phone, after the property holder realized that there was somebody before him and just opened the lock Savvy Entryway Lock by utilizing a cell phone if the property holder knows the guest. after guests see the green light the entryway has been opened, following a couple of moments the entryway will naturally lock once more. then, at that point, there is a press button from the indirect access to open the entryway in a crisis if the capacity of the cell phone doesn't attempt to open the entryway. the programmed work that I made in the entryway lock framework permits clients to effortlessly control and bind together the climate and states of the house without a moment's delay prior to going into or going out. Keywords: Smart Door Lock; Wireless; Smartphone; Android; Blynk;  Abstrak: Ulasan ini menggambarkan rencana IoT pada kunci pintu masuk Keen adalah kunci yang dapat digunakan untuk membuat kerangka keamanan yang masuk akal dan produktif di rumah dan bangunan lain. Sorotan pembaruan ditambahkan dengan Remote. Remote adalah jaringan telekomunikasi elektromagnetik yang memanfaatkan gelombang daripada tautan. Alasan di balik Kunci Pintu Masuk Keen ini adalah untuk meningkatkan keterampilan dan mengurangi pembukaan manual dari dalam, tetapi jika Anda membuka pintu dari sudut pandang eksternal, cukup menggunakan ponsel. dalam pemeriksaan, ketika tamu datang, tamu melihat peringatan sensor sebelum pintu masuk dan kemudian bergerak menuju sensor pemberitahuan yang telah direncanakan dengan aplikasi blynk sebelumnya, aplikasi blynk mengirimkan pemberitahuan melalui ponsel, setelah pemilik properti menyadari bahwa ada seseorang di depannya dan baru saja membuka kunci Savvy Entryway Lock dengan memanfaatkan ponsel jika pemilik properti mengenal tamu tersebut. setelah tamu melihat lampu hijau pintu masuk telah dibuka, beberapa saat kemudian pintu masuk secara alami akan terkunci kembali. Kemudian, pada saat itu, ada tombol tekan dari akses tidak langsung untuk membuka pintu dalam keadaan darurat jika kapasitas ponsel tidak berusaha untuk membuka pintu. Pekerjaan terprogram yang saya buat dalam kerangka kunci pintu memungkinkan klien untuk dengan mudah mengontrol keadaan rumah tanpa penundaan sesaat sebelum masuk atau keluar Kata kunci: Pintu Pintar; Wireless; Smarphone; Android; Blynk;